Investigação do estado da leishmaniose visceral canina no município de Lavras - MG - Narciso, Thiago Pasqua (2016)
Canine visceral leishmaniasis (CVL) is a zoonotic parasitic disease caused by Leishmania infantum. In Brazil, the main transmitter species is Lutzomyia longipalpis. By the year 2013, the city of Lavras was considered, according to the criteria established by the Manual of Surveillance and Control of Visceral Leishmaniasis, quiet area and not vulnerable to the LVC. Face to unofficial data of positive animals, it was necessary to investigate the epidemiological status of the LVC. Given these facts, this study aimed to investigate the status of the LVC in Lavras using molecular and serological techniques. The L. infantum infection was confirmed in spleen and bone marrow samples nine dogs subjected to qPCR. Four dogs were positive in both bone marrow and spleen samples. For the evaluation of serological tests, serum of 52 animals was submitted to DPP®, ELISA Canine Visceral Leishmaniasis - BioManguinhos and ELISA - rKDDR. Of the 52 animals, 40 were observed (75%) positive and 12 (25%) negative for the LVC DPP® Biomanguinhos and ELISA tests. After completion of the ELISA DDR, it was observed 34 (65%) positive animals and 18 (35%) negative animals, indicating that it is necessary a more detailed assessment of this material, in order to determine the presence or absence of cross-reactivity test DPP® and ELISA Biomanguinhos or a possible misdiagnosis ELISA rKDDR. Through the results of this project was confirmed by qPCR, the first case of canine infection by Leishmania infantum in Lavras-MG.